The Kinetics and Dry-Sliding Wear Properties of Boronized Gray Cast Iron - Dong Mu; Bao-luo Shen (Advances in Materials Science and Engineering)
Some properties of boride formed on gray cast iron (GCI) have been investigated. GCI was boronized by powder-pack method using Commercial LSB-II powders at 1123, 1173, and 1223 K for 2, 4, 6, and 8 h, respectively. Scanning electron microscopy showed that boride formed on the surface of boronized GCI had tooth-shaped morphology. The hardness of boride formed on surfaces of GCI ranged from 1619 to 1343 HV0.025, and quenched and tempered GCI ranged from 400 to 610 HV0.025. The boride formed in the coating layer confirmed by X-ray diffraction analysis was Fe2B single phase. Depending on boronizing time and temperature, the thickness of coating layers on boronized GCI ranged from 26 to 105 μm. The activation energy was 209 kJ/mol for boronized GCI. Moreover, the possibility of predicting the iso-thickness of boride layers variation was studied. Dry-sliding wear tests showed that the wear resistance of boronized sample was greater than that of quenched and tempered sample.